The Effectiveness of Baamboozle as Teaching Media to Improve Students’ Reading Comprehension of Recount Text - Khaeriyah; Atikah wati; Nasori Efendi (English Language Education Department, Universitas Majalengka, 2026)
This study aims to determine the effectiveness of Baamboozle in improving students’ reading comprehension of recount text. Low motivation and limited background knowledge are some of the reasons why students have difficulty understanding the text. This study used a quantitative design and was conducted at MTs Ma’arif Legok, involving 27 eighth-grade students. A pre-experimental design was employed, and the data were collected using random sampling with pre-test and post-test as the instruments. The data were analyzed using IBM SPSS Statistics version 20. Based on the results of the study, the mean score of the pre-test is 54,07 and the mean score of the post-test is 76,67. The normality test using the Shapiro-Wilk test showed that the significance values were higher than the significance level of 0.05 (0.111 > 0.05 and 0.169 > 0.05). This indicates that the data were normally distributed. Furthermore, the paired sample t-test revealed that (sig. 2-tailed) was 0.000, which is lower than the significance level of 0.05. Therefore, the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted. Thus, it can be concluded that the use of Baamboozle as a teaching media was effective in improving students’ reading comprehension of recount text. The researcher suggests that teachers use Baamboozle as an engaging alternative media for teaching reading comprehension. Future researchers are encouraged to examine its effectiveness in different contexts, levels, and language skills.